THEORETICAL ASPECTS OF ECONOMIC SECURITY IN CONTEMPORARY CONDITIONS (Development Service Industry Management, 2025)
The article examines the theoretical aspects of economic security in contemporary conditions. The article systematises approaches to determining the essence of an enterprise's economic security and summarises factors influencing economic security in terms of both internal and external factors. The components of economic security are systematised, and the expediency of considering such a component as energy security is substantiated. The systematization of approaches to determining the essence of economic security allowed us to define economic security as the ability to counteract threats, adapt to changes and ensure an adequate level of functioning through competitive advantages and effective functioning. The factors influencing the economic security of an enterprise are generally categorised into external and internal. The main internal factors influencing the economic security of an enterprise include: organizational and legal form, and form of ownership of the enterprise; resource potential; production potential; information support; level of competitiveness of the enterprise; quality of management; and financial support. The main external factors influencing the economic security of an enterprise include the economic situation in the region, country, and the world as a whole; the regulatory and legal environment; technological changes; the international environment; environmental factors; the level of socio-economic development; and the presence of martial law. The components of economic security are systematised, and the expediency of considering such a component as energy security is substantiated. The analysis revealed that economic security is a multifaceted concept comprising interconnected components. The complex functioning of the elements forms an integrated system of economic security of the enterprise, which ensures its ability to function effectively, respond promptly to the challenges of the external and internal environment and maintain long-term competitiveness. The interaction of the structural components of economic security is the foundation for ensuring the sustainable development of both an individual enterprise and the country's economy as a whole.
Keywords: economic security; influencing factors; energy security; financial scurity; personnel security